Efficiency and effectiveness of the European Parliament under the ordinary legislative procedure - Ani Matei; Cristina Ciora; Adrian Stelian Dumitru; Reli Ceche (Administrative Sciences, 2019)
In the aftermath of the 2019 European elections, the article tries to assess the efficiency and effectiveness of the European Parliament within the framework of the ordinary legislative procedure (co-decision). After defining and formulating the main indicators, the paper analyses the micro- and macro-performance of the European Parliament within the decision-making process from a quantitative-qualitative and a qualitative-quantitative perspective; highlighting the relativizing factors and the responsiveness of the European decision-making process to the Europeans' needs.
Keywords: 350; European parliament; ordinary legislative procedure; co-decision; efficiency; effectiveness